(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: The characteristics of newly diagnosed patients and the complications of Thalassemia patients diagnosed in childhood who survive into adulthood are often very diverse with different clinical and paraclinical features. Objective: Describe the results of treatment of primary nephrotic syndrome in children with Corticoids at Can Tho City Children’s Hospital in 2023-2024. Method: Retrospective description of over 40 pediatric patients diagnosed with Nephrotic Syndrome treated at Can Tho Children’s Hospital. Results: The proportion of men with the disease is the majority (82.5%) compared to women (17.5%). The majority of children with the disease are in the age group of 5-15 years old (85%). Most children were hospitalized due to edema symptoms (87.5%). The average duration of treatment is 10.75 ± 4.71 days, the shortest is 4 days and the longest is 20 days. After treatment, the average urea concentration was 5.97 mmol/L and the average blood creatinine was 44.26 µmol/L. Average proteinuria was 3.46 mg/kg/24h (1 - 10 mg/kg/24h). There were 77.5% of children whose edema decreased after treatment, 22.5% of children had completely no edema. 90% of children have improved or reduced symptoms of the syndrome. Conclusion: Corticosteroids have proven to be an effective treatment for nephrotic syndrome in children, providing good control of clinical symptoms. However, it is still necessary to consider combining other drugs to better control paraclinical indicators, limit recurrence and long-term complications.